Мент обиды не прощает: [роман] / Владимир Николаев - Николаев Владимир Николаевич (Серия "Черная кошка", 1999)
Экземпляры: ф.14 (20160720) / Инвентарный номер: 51994 / Цена: 10.00 / Авт.знак: Н 63 / ББК: 84(2Рос=Рус)6